2017
DOI: 10.1002/jbm.a.36274
|View full text |Cite
|
Sign up to set email alerts
|

Time course study of long‐term biocompatibility and foreign body reaction to intraneural polyimide‐based implants

Abstract: The foreign body reaction (FBR) against an implanted device is characterized by the formation of a fibrotic tissue around the implant. In the case of interfaces for peripheral nerves, used to stimulate specific group of axons and to record different nerve signals, the FBR induces a matrix deposition around the implant creating a physical separation between nerve fibers and the interface that may reduce its functionality over time. In order to understand how the FBR to intraneural interfaces evolves, polyimide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…Specifically, the encapsulation thickness surrounding the SW implanted nerves was ≈12 µm compared to its PW counterpart, ≈30 µm. Encapsulation (30 µm) is similar to the values reported in Olivia et al evaluating the chronic foreign body response of tf‐LIFE electrodes at 4 weeks (≈23 µm) . PW showed significant reduction in axon size, compared to sham and SW implants across all bins (Figure d).…”
Section: Introductionsupporting
confidence: 80%
“…Specifically, the encapsulation thickness surrounding the SW implanted nerves was ≈12 µm compared to its PW counterpart, ≈30 µm. Encapsulation (30 µm) is similar to the values reported in Olivia et al evaluating the chronic foreign body response of tf‐LIFE electrodes at 4 weeks (≈23 µm) . PW showed significant reduction in axon size, compared to sham and SW implants across all bins (Figure d).…”
Section: Introductionsupporting
confidence: 80%
“…We have recently characterized the extent of the inflammatory and the remodeling phases of the FBR to longitudinal implants in the peripheral nerve (De la Oliva, Navarro, and del Valle, ), thus determining possible targets for reducing the encapsulation and improving electrode functional outcome. The aim of this study is to evaluate the effect of different treatments to modulate the FBR and to reduce capsule thickness around longitudinal parylene C intraneural implants inserted in the rat sciatic nerve.…”
mentioning
confidence: 99%
“…The biocompatibility of various surfaces including SU‐8, Parylene‐C, polyimide, and polydimethylsiloxane (PDMS) has been recently investigated with positive outcomes, especially where the surfaces were nanostructured in later manufacturing processes . Extended in vivo studies showed that Parylene‐C had good chemical stability and low glial scarring for small implants, but had enhanced tissue encapsulation compared to polyimide in chronically implanted peripheral interfaces …”
Section: Biocompatibilitymentioning
confidence: 99%